Well-differentiated fetal adenocarcinoma of the lung: positron emission tomography features and diagnostic difficulties in frozen section analysis—a case report - Shuhei Hakiri; Takayuki Fukui; Hideki Tsubouchi; Ayako Sakakibara; Shingo Iwano; Toyofumi F. Chen-Yoshikawa (Surgical Case Reports)
Abstract Background Well-differentiated fetal adenocarcinoma (WDFA) of the lung is a rare disease that resembles fetal lung tubules. Most of previous reports concerning WDFA have focused on histological features, while there are few reports describing radiological features. In addition, there are no reports evaluating the difficulty of intraoperative diagnosis of WDFA with frozen section. We report a case of WDFA and review the radiological features of WDFA including the findings of F-18 fluorodeoxyglucose positron emission tomography (FDG-PET) and assess the difficulty of intraoperative diagnosis with frozen section. Case presentation A chest radiography performed in a 20-year-old female revealed a mass in the hilum of the right lung. Computed tomography revealed a well-defined mass measuring 3.5 × 3.0 cm in diameter in the right upper lobe, whereas PET showed a high accumulation of FDG. The most likely diagnosis was clinical T2aN0M0 stage 1B non-small cell lung cancer. A right S3 segmentectomy was performed via thoracotomy, and a benign tumor that was possibly an adenoma was intraoperatively diagnosed based on frozen section analysis. The mass was a solid tumor measuring 2.9 × 2.5 cm in diameter. Microscopically, the tumor comprised abundant glands with single or double layers of nonciliated cells and bronchial structures resembling a fetal lung. Rounded morules of polygonal cells were frequently observed. Immunohistochemistry revealed that nuclei and cytoplasm of the tumor cell were positive for β-catenin. Finally, the postoperative pathological diagnosis was well-differentiated fetal adenocarcinoma of the lung, and completion right upper lobectomy and mediastinal lymph node dissection were conducted 1 month after the initial segmentectomy. No residual tumor or lymph node metastasis was identified, and the final pathological stage was pT1cN0M0 stage 1A3. The patient did not wish to receive any adjuvant therapy. At the 1-year follow-up, no evidence of recurrence was noted. Conclusions Here, we report a rare case of well-differentiated fetal adenocarcinoma of the lung that was difficult to diagnose based on radiological evaluations including FDG-PET and intraoperative diagnosis using frozen section analysis.